Production and recycling of the cutting edge material of gallium: A review - Guan, Tangzhen; Guo, Minghui; Wang, Lei; Liu, Jing (The Science of the total environment, 2025)
Gallium, an indispensable scattering element, is driving the development of an array of latest generation functional materials. Due to its exceptionally conductive, fluidic, thermal, flexible, and biocompatible attributes, gallium and its derivatives are increasingly introduced into diverse cutting edge industries. Meanwhile, the aggravated irreconcilable contradiction between the rapid growth of gallium consumption and the severe shortage of gallium resources also brings about big concern regarding its availability for the coming era. In this review, we conducted a comprehensive examination on the global distribution and reserves of gallium which indicates sporadic locations and low concentrations of gallium, highlighting the daunting challenge of extracting gallium. Following that, extensive assessments of gallium production and recovery treatments were presented, ranging from ore mining to high-purity gallium extraction, from major to minor production methods, and from primary gallium extraction to recycling gallium reclamation. Finally, based on evaluating ongoing trends over the field, a forecast of the future gallium production and recycling was given. Potential barriers and their corresponding mitigation strategies were interpreted. [Display omitted] •A comprehensive review of gallium resource circulation, covering production, applications, and recycling.•Overview of the global distribution and reserves of gallium.•Comparison of methods for extracting gallium from bauxite.•Discussion on gallium production from various raw materials and recycling from waste.•Strategies and directions for expanding gallium resource acquisition are proposed.